132 Quality Improvement Project (QIP) On Compliance of Vascular Society's Clinical Care Pathway for Patients with Critical Limb Ischaemia (CLI) Admitted to Vascular Ward At Worcestershire Royal Hospital (WRH). (4th May 2021) - Mehta, A; Meecham, L; Shakarchi, J Al; Charlwood, N
Abstract: Introduction: Patients often present to the emergency department with critical limb ischaemia (CLI). According to the Vascular Society 2019 guidelines, these patients require. Vascular surgeon face-to-face review within 14 hours, Cross-sectional imaging with CTA/ MRA within 12 hours and, Revascularization ≤ 5 days. All metrics should be carried out >80% of the time. Method: A QIP was conducted of all CLI patients admitted with rapid progression/ deep tissue injury/ rest pain at WRH between 23/01/2020-31/03/2020. Sources of data - Patient records, ICE and PACS Results: Compliance target for below were not met. Cross-sectional imaging within 12 hours - 12.5% (delayed due to other emergency scans/ ward team delay requesting scans within 12 hours) Revascularization ≤ 5 days - 75% (Interventional Radiology delayed procedures to deal with non-vascular emergencies, patients needing medical optimization before being declared fit for surgery). However, compliance for vascular surgeon face-to-face review within 14 hours stood at 100%. Conclusions: Failure to fully comply could lead to poor prognostic outcomes such as loss of limb or death. Consequently, the WRH vascular governance board agreed to put the following measures in place. Dedicated daily imaging slots for vascular patients. Weekly theatre slots for vascular emergency cases.